Half-Sib Lines of Pedunculate Oak (Quercus robur L.) Respond Differently to Drought Through Biometrical, Anatomical and Physiological Traits - Erna Vastag (Forests, 2020)
Quercus robur L. is one of the most valued tree species of deciduous temperate forests. However, in the last decade, serious oak declines and loss of adaptation plasticity have been reported throughout Europe as a consequence of drought. Therefore, the aim of the present study was to define the adaptation potential of five Q. robur half-sib lines from the UNESCO Biosphere Reserve Mura-Drava-Danube to drought, using physiological, anatomical and biometrical traits. Half-sib lines that exhibited drought tolerance had particular suites of trait expression regarding biometrical traits (seedling height, root length, root to shoot ratio of dry mass and specific leaf area), leaf stomatal traits (stomatal density per mm2, stomata guard cell length and width, stomatal aperture length and width) and leaf structural traits (adaxial epidermis thickness, palisade parenchyma thickness, spongy parenchyma thickness, lamina thickness). All of the observed parameters of chlorophyll a fluorescence were shown to be good indicators of short-term and severe drought. For the selection of drought-tolerant half-sib lines, all studied chlorophyll a fluorescence parameters associated with the heat dissipation of light energy (coefficient of non-photochemical quenching, quantum yield of regulated energy dissipation, Stern-Volmer type non-photochemical fluorescence quenching) and one parameter related to photochemical dissipation of light energy (effective quantum yield (efficiency) of PS II photochemistry) were proven to be suitable. On the other hand, the coefficient of photochemical quenching, coefficient of photochemical fluorescence quenching assuming interconnected photosystem II antennae and electron transport rate were not suitable for distinguishing the different responses of the studied half-sib lines under drought. The importance of results of the present study is in the selection of drought-tolerant Q. robur half-sib lines for future reforestation programs, particularly in protected areas with sensitive forest management and restricted activities for mitigation of the adverse effects of climate changes.